REVIEWS (New blackfriars, 1971)
Reviews in this article THE GOOD NEWS ACCORDING TO MARK, by Eduard Schweizer. HOPE AND PLANNING, by Jurgen Moltmann. FOI SANS METAPHYSIQUE NI THEOLOGIE, by Dario Antiseri.